2019
DOI: 10.1186/s12877-019-1307-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the geriatric quality of life-dementia in older adults with dementia or mild cognitive impairment living in nursing homes

Abstract: BackgroundGiven the theoretical and methodological limitations, there is insufficient knowledge about the psychometric properties and internal structure of quality of life (QOL) measurements for patients with dementia living in nursing homes. The present study aimed to confirm the validity and reliability of the Geriatric Quality of Life-Dementia scale (GQOL-D) to measure the QOL of patients with dementia in nursing homes and analyze their QOL based on the validated GQOL-D factor structure.MethodsThe GQOL-D wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Regarding WS and a cognitive function, the concept of frailty has become a geriatric topic recently. Although we could not include frailty as global score in the correlation analysis or binomial regression analysis because the distribution of a frail group according to the frailty phenotype was greatly biased (e.g., % of robust/pre-frail/frail, 50%/50%/0% in the non-MCI group, 43%/47%/10% in the MCI group) (Table 1), some studies have reported that a physical frailty is associated with MCI and a reduction of WS in five items of the Fried index mostly reflect the occurrence of MCI and disability [31,53]. MCI with concomitant physical frailty may be considered to fulfil the criteria for cognitive frailty [54].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding WS and a cognitive function, the concept of frailty has become a geriatric topic recently. Although we could not include frailty as global score in the correlation analysis or binomial regression analysis because the distribution of a frail group according to the frailty phenotype was greatly biased (e.g., % of robust/pre-frail/frail, 50%/50%/0% in the non-MCI group, 43%/47%/10% in the MCI group) (Table 1), some studies have reported that a physical frailty is associated with MCI and a reduction of WS in five items of the Fried index mostly reflect the occurrence of MCI and disability [31,53]. MCI with concomitant physical frailty may be considered to fulfil the criteria for cognitive frailty [54].…”
Section: Discussionmentioning
confidence: 99%
“…The source of the data was a large-scale research project focused on BPSD to develop an intervention program for improving quality of life. Details of the sampling process have been reported in Park et al [42].…”
Section: Phase 1: Psychological Needs To Relieve Symptomsmentioning
confidence: 99%
“…Most of the nursing home residents in Jordan are not admitted based on specific medical admission criteria [ 10 ], which indicates that information is still limited regarding their healthcare needs as well as factors influencing their cognitive ability. Numerous factors were found to be associated with cognitive impairment or the risk of incidental dementia, such as frailty [ 11 ], depression [ 12 ], and health-related quality of life (HRQoL) [ 13 , 14 ]. However, the factors of transition from mild cognitive impairment to moderate cognitive impairment stage or dementia among older adults have not been extensively understood in the literature.…”
Section: Introductionmentioning
confidence: 99%